Dietary intake of 4-nonylphenol and bisphenol A in Taiwanese population: Integrated risk assessment based on probabilistic and sensitive approach. (January 2019) - Chang, Wei-Hsiang; Liu, Shou-Chun; Chen, Hsiu-Ling; Lee, Ching-Chang
Abstract: 4-Nonylphenol (NP) and bisphenol A (BPA) are high-production and high-volume chemicals used to manufacture various commercial products. They are also ubiquitous contaminants that disrupt endocrine systems in wildlife and humans. We collected, from Taiwan cities with the highest food production, and analyzed, using high performance liquid chromatography tandem mass spectrometry (HPLC/MS/MS), 278 food samples for NP and BPA from 11 categories. We found background levels of 100% for NP and 72% for BPA in total samples. High levels of contamination (up to 918 and 49.4 μg/kg) were found in some foods of seafood and animal origin. We used a probabilistic approach to calculate daily dietary dose (Monte Carlo-estimated 95th percentile dietary exposure [MCS 95]) from the Taiwan National Food Consumption database for each sex- and age-specified population. For NP and BPA, the highest average daily dose (ADDs) were in the 4- to 6-year-old group (MCS 95 = 1.57/1.28 and 0.157/0.147 [Male/Female] μg/kg bw/day, respectively), and the lowest ADDs were in the ≥65-year-old group (MCS 95 = 0.674/0.581 and 0.054/0.045 [M/F] μg/kg bw/day, respectively). Based on the European Food Safety Authority (4 μg/kg bw/day for BPA) and Danish Institute of Safety and Toxicology guidelines (5 μg/kg bw/day for NP), the 95th percentile HQ of NP and BPA intake in different sex- and age-specified groups in Taiwan posed no risks through dietary exposure. The intake quantity and concentrations of grains, livestock, and seafood are important variables for the integrated risk of NP and BPA. In conclusion, a combination of multiple and long-term exposure via food consumption should be considered rather than individual endocrine-disrupting chemicals during dietary risk assessment in specific populations. Summary: The 95th percentile HQ of NP and BPA intake in different age and sex groups in Taiwan posed no risks through dietary exposure based on probabilistic and sensitive approach. Graphical abstract: Image 1 Highlights: The highest concentration of nonylphenol (NP) was in crustaceans, and of bisphenol A (BPA) was in canned foods. Whole grains, meat, and seafood are the sensitive ingredients for the integrated risk of NP and BPA. The daily doses (MCS 95) of NP and BPA were in the 4- to 6-year-old group; both were below the suggested TDI. The 95th HQ of NP and BPA intake in different age and sex groups in Taiwan posed no risks through dietary exposure.